2012
DOI: 10.3748/wjg.v18.i9.930
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of sulphate-bicarbonate-calcium water on gallstone risk and weight control

Abstract: Sulphate-bicarbonate-calcium water consumption has a positive effect on lithogenic risk and intestinal transit and allows maintenance of a stable body weight despite a high food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 40 publications
0
23
1
2
Order By: Relevance
“…Sulfates have been shown to have positive effects on the gallbladder; however, the sulfate-rich mineral water investigated did not show effects on liver enzymes [33]. Similarly, there were no improvements on blood lipids either; however, the results produced by other studies of sulfate-containing mineral water on blood lipids are contradictory [15,26].…”
Section: Discussioncontrasting
confidence: 45%
“…Sulfates have been shown to have positive effects on the gallbladder; however, the sulfate-rich mineral water investigated did not show effects on liver enzymes [33]. Similarly, there were no improvements on blood lipids either; however, the results produced by other studies of sulfate-containing mineral water on blood lipids are contradictory [15,26].…”
Section: Discussioncontrasting
confidence: 45%
“…Stoicescu et al study the infl uence of Lipova bicarbonate calcic water on experimental models with alloxan induced diabetes. Th e authors observed a lower increase of the glycemic level (42% increase in alloxan group compared with alloxan and mineral water which presented statistical signifi cance) 24 .…”
Section: Discussionmentioning
confidence: 89%
“…Corradini et al. 14 have shown a beneficial effect of the hydropinic treatment with sulphate-bicarbonate-calcium mineral waters in reducing the risk of biliary calculi and favoring weight control. Moreover, the same spa treatment with sulphate-calcium mineral waters may effectively normalize the echoscopy picture and the motor function of stomach and gallbladder.…”
Section: Current Resultsmentioning
confidence: 99%